Post‐translational modifications of histones: Mechanisms, biological functions, and therapeutic targets - Ruiqi Liu; Jiajun Wu; Haiwei Guo; Weiping Yao; Shuang Li; Yanwei Lu; Yongshi Jia; Xiaodong Liang; Jianming Tang; Haibo Zhang (MedComm, 2023)
Abstract Histones are DNA‐binding basic proteins found in chromosomes. After the histone translation, its amino tail undergoes various modifications, such as methylation, acetylation, phosphorylation, ubiquitination, malonylation, propionylation, butyrylation, crotonylation, and lactylation, which together constitute the “histone code.” The relationship between their combination and biological function can be used as an important epigenetic marker. Methylation and demethylation of the same histone residue, acetylation and deacetylation, phosphorylation and dephosphorylation, and even methylation and acetylation between different histone residues cooperate or antagonize with each other, forming a complex network. Histone‐modifying enzymes, which cause numerous histone codes, have become a hot topic in the research on cancer therapeutic targets. Therefore, a thorough understanding of the role of histone post‐translational modifications (PTMs) in cell life activities is very important for preventing and treating human diseases. In this review, several most thoroughly studied and newly discovered histone PTMs are introduced. Furthermore, we focus on the histone‐modifying enzymes with carcinogenic potential, their abnormal modification sites in various tumors, and multiple essential molecular regulation mechanism. Finally, we summarize the missing areas of the current research and point out the direction of future research. We hope to provide a comprehensive understanding and promote further research in this field.